Pemberian Daun Lamtoro (Leucaena Leucocephala) dalam Ransum Terhadap Performa Broiler - M, Mihrani; Fathanah, Siti Yasya Ey; Beddu, Hartina (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aimed at finding out the effect of the provision of lamtoro leaves in the ration on the weight gain, feed consumption, and feed conversion in broilers. This study was conducted from March to May 2023, Romang Lompoa, Bontomarannu, Gowa Regency, South Sulawesi. In this study, the researcher applied a completely randomized design (CRD) with 4 treatments and 4 replications in which each replication consisted of 3 broilers. The treatments were given in the rations of broilers aged 1-29 days. The treatments consisted of rations without any treatment (P0), rations with 5% lamtoro leaves (P1), rations with 7.5% lamtoro leaves (P2), and rations with 10% lamtoro leaves (P3). The observed parameters were body weight gain, feed consumption, and feed conversion. The employed data analyses were the ANOVA test and Duncan’s test. Results showed that the provision of lamtoro leaves in the ration gave a significant effect (p < 0.05) on weight gain and feed consumption of broilers, but did not have a significant effect (p > 0.05) on feed conversion. Based on the data of each parameter tested with various treatments, it can be recommended that the best treatment is the provision of 5% lamtoro leaves (P1).